2018
DOI: 10.3390/ani8110196
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Associated with Marine Lipid-Induced Milk Fat Depression in Sheep Cause Shifts in the In Vitro Ruminal Metabolism of 1-13C Oleic Acid

Abstract: Simple SummaryDairy ewes, just like cows, suffer from the low-fat milk syndrome, also known as milk fat depression (MFD), when marine lipids are added to their diet to modulate milk fatty acid (FA) profile. Alterations in the ruminal metabolism of dietary unsaturated FA seem to be at the core of this MFD but its causative agent has not yet been confirmed. Although some alterations may derive from shifts in oleic acid metabolism, methodological constraints represent a major challenge: the fact that oleic and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Several recent in vivo studies have observed a positive association between MFD and the milk fat proportion of oxo-FA, particularly 10-oxo-18:0, in cows, ewes and does fed fish oil (Bernard et al, 2015;Kairenius et al, 2015;Carreño et al, 2016). Those increments in 10-oxo-18:0 may derive from alterations in the relative contribution of specific pathways of ruminal cis-9 18:1 metabolism, as suggested in an in vitro study with rumen inoculum of sheep adapted to fish oil consumption (Toral et al, 2018b). Overall, these observations support the potential involvement of oxo-FA, and of 10oxo-18:0 in particular, in marine lipid-induced MFD.…”
Section: Biohydrogenation Intermediates Associated With Mfdmentioning
confidence: 87%
See 2 more Smart Citations
“…Several recent in vivo studies have observed a positive association between MFD and the milk fat proportion of oxo-FA, particularly 10-oxo-18:0, in cows, ewes and does fed fish oil (Bernard et al, 2015;Kairenius et al, 2015;Carreño et al, 2016). Those increments in 10-oxo-18:0 may derive from alterations in the relative contribution of specific pathways of ruminal cis-9 18:1 metabolism, as suggested in an in vitro study with rumen inoculum of sheep adapted to fish oil consumption (Toral et al, 2018b). Overall, these observations support the potential involvement of oxo-FA, and of 10oxo-18:0 in particular, in marine lipid-induced MFD.…”
Section: Biohydrogenation Intermediates Associated With Mfdmentioning
confidence: 87%
“…For example, the increased milk fat proportion of cis-11 18:1 under fish oil-induced MFD conditions (Shingfield et al, 2003;Kairenius et al, 2015) might result from its supply of marine lipids and the concomitant inhibition of 18:1 saturation, rather than from an increased production in the rumen through C18 biohydrogenation. This hypothesis is supported by the in vitro incubation of 13 C-labeled UFA with rumen inoculum from cows (Klein and Jenkins, 2011) or from sheep adapted or not to fish oil consumption (Toral et al, 2018b. As such, PUFA originating directly from fish oil might contribute, at least in part, to MFD.…”
Section: Biohydrogenation Intermediates Associated With Mfdmentioning
confidence: 88%
See 1 more Smart Citation
“…Regarding the impact of OO on milk fat composition, it is worth highlighting some desirable effects, such as the decrease in medium-chain saturated FA and the increase in some potentially health-promoting compounds, specifically 4:0, trans -11 18:1, cis -9 trans -11 CLA, and cis -9 18:1 [ 1 , 39 ]. The large variation in the latter would derive not only from dietary cis -9 18:1 supply, but also from its extensive saturation in the rumen [ 45 , 46 ], enhancing the availability of 18:0 for mammary Δ 9 -desaturation [ 47 ]. Ruminal cis -9 18:1 metabolism also involves isomerization and hydration/oxidation processes [ 45 , 46 ], which would partly explain the increments in milk trans 18:1 and 10-oxo-18:0, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial digestion of fiber and other nutrients in the gum stomachs of the ruminants indicates the nature of the influence of the formed and used metabolites of the substrate [1]. As a result of the relative values of some key processes, primarily lipogenesis in ruminants, it differs significantly from similar processes and nonruminant ones.…”
Section: Introductionmentioning
confidence: 99%